2000
DOI: 10.1002/(sici)1099-0518(20000101)38:1<18::aid-pola3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Application ofS-alkylsulfonium salts of aromatic sulfides as new thermal latent cationic initiators

Abstract: The cationic initiation activity of derivatives of S‐methylsulfonium salts of dibenzothiophene (3a), diphenyl sulfide (4a), thioanisole (4d), and tetrahydrothiophene (5) was evaluated in the polymerization of glycidyl phenyl ether (1). These initiators were soluble in 1 and capable of initiating the cationic polymerization of 1 on heating, with the exception of methyltetrahydrothiophenium tetrafluoroborate (5; in the range of room temperature to 160 °C). Among them, methyldiphenylsulfonium tetrafluoroborate (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…More‐than‐four‐membered sulfide‐containing rings do not show any significant ring‐opening polymerisation activity either via anionic70 or cationic mechanisms, while the corresponding cyclic ethers (e.g., tetrahydrofuran) can be polymerised through a cationic mechanism. It is noteworthy that the stability of sulfonium ions in large rings has been usefully employed in the cationic ring‐opening of the ethers, for which either cyclic sulfonium ions can be used as cationic initiators,71 acting as an alkylating agent (Scheme ), or cyclic thioethers can be been used as chain terminators72 (Scheme ).…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…More‐than‐four‐membered sulfide‐containing rings do not show any significant ring‐opening polymerisation activity either via anionic70 or cationic mechanisms, while the corresponding cyclic ethers (e.g., tetrahydrofuran) can be polymerised through a cationic mechanism. It is noteworthy that the stability of sulfonium ions in large rings has been usefully employed in the cationic ring‐opening of the ethers, for which either cyclic sulfonium ions can be used as cationic initiators,71 acting as an alkylating agent (Scheme ), or cyclic thioethers can be been used as chain terminators72 (Scheme ).…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…These catalysts can initiate polymerization under external impetus such as thermal or photo irradiation. Various kinds of latent catalysts are used in the polymerization reaction such as sulfonium salt [1][2][3][4], phosphonium salt [5], pyrazinium salt [6], N-heterocyclic carbene [7], aminimide [8], and sulfonate [9]. We have previously reported that primary alkylamines intercalated with α-zirconium phosphate (α-ZrP) can serve as latent thermal initiators in the reaction of glycidyl phenyl ether (GPE) [10] and that intercalation compounds of 1,4-diazabicyclo(2,2,2)octane (DABCO) and 1,8-diazabicyclo(5,4,0)undec-7-ene (DBU) with α-ZrP: α-ZrP·DABCO and α-ZrP·DBU show good performance as latent thermal catalysts in the reaction of GPE with hexahydro-4-methylphthalic anhydride (MHHPA) [11].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that several sulfonium [328][329][330][331][332][333][334][335][336], phosphonium [67,68,[337][338][339][340], pyridinium [296,298,[341][342][343][344] and other N-containing onium salts [345][346][347] could serve as latent thermal cationic initiators for epoxy polymerization. They observed that their initiating activity could be efficiently controlled through the variation of the electronic and steric properties of their substituents.…”
Section: Thermolatent Onium Salts Initiatormentioning
confidence: 99%